1998
DOI: 10.1590/s1020-49891998000500004
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura do exame citopatológico na cidade de Pelotas, Brasil

Abstract: In 1995, cervical cancer was the fourth most important cause of death among women in the state of Rio Grande do Sul, Brazil. There are no available studies on Pap smear examination coverage in Pelotas, which is the largest city in the southern part of Rio Grande do Sul. Accordingly, in 1992 a population-based, cross-sectional study was carried out among 20 to 69 year-old women residing in urban areas of the city. The objectives of the study were to ascertain any Pap smear testing in the 3 years prior to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
12

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
2
0
12
Order By: Relevance
“…Some studies have found lower rates of cervical cancer screening among younger women (15-24 years old, less than 20 years old, 15-29 years old, 25-29 years old), while others have found them among older age groups (50-69 years old, 60-69 years old, and 55-59 years old). 4 Nascimento et al, 5 Costa et al, 3 and Quadros et al 8 found high rates of cervical cancer screening failure among women who had never undergone breast self-examination and did not attend medical visits in the year prior to the study, which was not evaluated in the present study.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Some studies have found lower rates of cervical cancer screening among younger women (15-24 years old, less than 20 years old, 15-29 years old, 25-29 years old), while others have found them among older age groups (50-69 years old, 60-69 years old, and 55-59 years old). 4 Nascimento et al, 5 Costa et al, 3 and Quadros et al 8 found high rates of cervical cancer screening failure among women who had never undergone breast self-examination and did not attend medical visits in the year prior to the study, which was not evaluated in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…Pinho et al 6 reported that the main reasons for not undergoing testing were: not having gynecological problems, being embarrassed or afraid of undergoing testing, and reported diffi culty in gaining access to a health care unit. In another study, Costa et al 3 concluded that the lower the social condition the less women would undergo cervical screening and that coverage was lower in older women. Quadros et al 8 showed that black and low income women were proportionally less likely to undergo screening.…”
Section: Conclusõesmentioning
confidence: 98%
“…Em São Paulo, a realização do Papanicolaou pelo menos uma vez na vida passou de 68,9% em 1987 13 para 86,1% em 2000 14 . Em Pelotas, a realização do preventivo nos últimos três anos foi de 65% em 1992 15 , 72,2% em 1999/2000 16 e 68,8% em 2002 17 . Em 1994, segundo pesquisa feita pelo Ibope, 64% das mulheres com mais de 15 anos de idade haviam feito o exame pelo menos uma vez na vida 1 .…”
Section: Introductionunclassified
“…Como se observa, as mulheres conviviam com insuficientes recursos financeiros. Segundo informações gerais, mulheres mais pobres apresentam mais comprometimento do câncer cérvico-uterino (11) . Em reforço à idéia anterior, pesquisadores afirmam que as dificuldades socio-econômicas agem como facilitadores ou como barreiras de acesso aos serviços de saúde (12) .…”
Section: Resultsunclassified